Theoretical investigation of lithium-atom insertion into ultra-small diameter carbon nanotubes - Anurak Udomvech (2018)
Computations of Li intercalation into ultra-small single-walled carbon nanotubes have been carried out within the framework of the first-principles density functional calculation. The energy and the structural properties of two Li atoms as a function of distance along the longitudinal axis of (3,3), (4,2) and (5,0) nanotubes have been calculated. We found that Li atoms could be easily pulled into the interior of (3,3) and (4,2) nanotubes whereas a small energy barrier existed at the open-mount of (5,0) tube. The zigzag (5,0) nanotube allows Li-Li to localize near the tube center, forming a Li2cluster inside the nanotube. In contrast, Li atoms prefer to locate near the open mounts of the armchair (3,3) tube. In case of a (4,2) nanotube, no preferential location is found, as described by the flat potential energy profile. The intercalated atoms affect the geometric parameters at the central region more than the rest of the nanotube. These results provide evidence that chirality plays a crucial role in Li-tube interactions, especially for ultra-small nanotubes, which suggests that appropriate tubule chiralities are needed if efficient anode materials are to be used in Li batteries.